Thermoelectric Properties of YBa 2 Cu 3 O 7−x -Ca 3 Co 4 O 9 Segmented Oxide Ceramic - Pimpilai Wannasut (2019)
© 2019, The Minerals, Metals & Materials Society. YBa 2 Cu 3 O 7-x -Ca 3 Co 4 O 9 (YBCO-CCO) segmented ceramic was prepared successfully using a conventional solid state sintering technique. X-ray diffraction patterns and microstructural observation indicated phase purity and a compatibility of YBCO and CCO ceramics. The maximum values of electrical conductivity (σ), Seebeck coefficient (S) and figure of merit (ZT) of YBCO-CCO segmented ceramic were 1.23 × 10 4 Ω −1  m −1 , 179 μV/K and 0.35, respectively. Meanwhile, the thermal conductivity (κ) values of these three compounds were not significantly different and possessed small temperature dependence. The enhancement in the ZT values of YBCO-CCO segmented ceramic at high temperature compared to the conventional CCO ceramic suggested that the former might be used as an alternative p-type material for thermoelectric devices.